Quality of care for children with acute malnutrition at health center level in Uganda: a cross sectional study in West Nile region during the refugee crisis. - Wanzira, Humphrey; Muyinda, Richard; Lochoro, Peter; Putoto, Giovanni; Segafredo, Giulia; Wamani, Henry; Lazzerini, Marzia (BMC Health Serv Res, 2018)
BACKGROUND: Arua district, in Uganda, hosts some of the largest refugee camps in the country. The estimated prevalence of moderate and severe acute malnutrition in children is higher than the national estimates (10.4 and 5.6% respectively, compared to 3.6 and 1.3%). This study aimed at assessing the quality of care provided to children with acute malnutrition at out-patient level in such a setting. METHODS: Six facilities with the highest number of children with malnutrition were selected. The main tool used was the National Nutrition Service Delivery Assessment Tool, assessing 10 key areas of service delivery and assigned a score as either poor, fair, good or excellent. Health outcomes, quality of case management and data quality were assessed from the health management information system and from the official nutrition registers. RESULTS: All facilities except two scored either poor or fair under all the 10 assessment areas. Overall, 33/60 (55%) areas scored as poor, 25/60 (41%) as fair, 2/60 (3.3%) as good, and none as excellent. Main gaps identified included: lack of trained staff; disorganised patient flow; poor case management; stock out of essential supplies including ready-to-use therapeutic foods; weak community linkage. A sample coverage of 45.4% (1020/2248) of total children admitted in the district during the 2016 financial year were included. The overall mean cure rate was 52.9% while the default rate was 38.3%. There was great heterogeneity across health facilities in health outcomes, quality of case management, and data quality. CONCLUSION: This study suggests that quality of care provided to children with malnutrition at health center level is substandard with unacceptable low cure rates. It is essential to identify effective approaches to enhance adherence to national guidelines, provision of essential nutritional commodities, regular monitoring of services and better linkage with the community through village health teams.
Keywords: Child Nutrition Disorders; Child, Preschool; Cross-Sectional Studies; Health Facilities; Humans; Nutrition Assessment; Nutritional Status; Prevalence; Quality of Health Care; Refugee Camps; Refugees; Uganda

Qualitative questionnaire on the psychosocial wellbeing of mothers of children with BEEC. - Di Grazia, Massimo; Pellizzoni, Sandra; Tonegatti, Luca Giacomo; Rigamonti, Waifro (J Pediatr Urol, 2017)
INTRODUCTION: The bladder exstrophy-epispadias complex (BEEC) represents a spectrum of malformations that affect the anatomical and functional structure of the urogenital system. The parents of patients affected by this condition are subject to particularly stressful situations, such as worrying about their child's health, long hospital stays, concerns about the health and constant need for personal care for their children, that can profoundly compromise the quality of family life. OBJECTIVE: The objective of this explorative qualitative study is to evaluate the social situation and the psychological strategies implemented by the mothers of children between 6 and 10 years of age who are affected by BEEC. STUDY DESIGN: Fourteen mothers of children aged 6-10 years and affected by BEEC (9 boys and 5 girls) were interviewed. Data on the mothers' experiences were collected through semi-structured interviews (Table). RESULTS: The qualitative analysis of the interviews showed that participants described experiences that were characterised by emotions such as fear and anger. Each mother had implemented a different and, sometimes, dysfunctional strategy in order to cope with the complex situation of the son/daughter. The aspects that most clearly emerged from mothers' descriptions were (1) the traumatic situation at the birth of the baby, (2) the sense of embarrassment concerning the pathological condition as the child was growing and the consequent sense of isolation of the mother, and (3) the fluctuation of feelings towards the multidisciplinary staff, which was sometimes seen as an important source of help and some other times as too destabilising and not helpful at all. DISCUSSION: The study provided some insight into the psychological and social conditions experienced by mothers of children with BEEC, which could serve as a basis for developing multidisciplinary teams with greater awareness about families living with this condition and better timing in addressing their needs. CONCLUSIONS: Mothers of children with BEEC show emotional and social difficulties. This is a crucial aspect to consider when planning a multidisciplinary approach to the treatment/therapy, especially considering that children examined in this study are approaching adolescence.
Keywords: Adaptation, Psychological; Adolescent; Bladder Exstrophy; Child; Epispadias; Female; Humans; Long-Term Care; Male; Mother-Child Relations; Mothers; Qualitative Research; Quality of Life; Stress, Psychological; Surveys and Questionnaires; Treatment Outcome

A quasi randomized-controlled trial to evaluate the effectiveness of clowntherapy on children's anxiety and pain levels in emergency department. - Felluga, Margherita; Rabach, Ingrid; Minute, Marta; Montico, Marcella; Giorgi, Rita; Lonciari, Isabella; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2016)
UNLABELLED: The aim of the study is to investigate if the presence of medical clowns during painful procedures in the emergency department (ED) affects children's anxiety and pain. Forty children (4-11 years) admitted to the ED with the need of painful procedures were prospectively enrolled. They were randomly assigned to the clown group, where children interacted with clowns or to the control group in which they were entertained by parents and ED nurses. The children's anxiety was assessed by the Children's Anxiety and Pain Scales; pain was evaluated with the Numerical Rating Scale and Wong-Backer Scale, according to the children's age. Staff and clown's opinions were evaluated by means of dedicated questionnaires. Children's anxiety levels in the clown group were significantly lower than those compared with the control group, while children's pain levels did not change between the two groups. CONCLUSION: The presence of clowns in the ED before and during painful procedures was effective in reducing children's anxiety. WHAT IS KNOWN: • Anxiety and fear caused by medical procedures exacerbate children's pain and may interfere with the procedure. • To reduce anxiety, fear, and pain and to facilitate patient's evaluation, different non-pharmacological approaches have been proposed and positive effects of laughter and humor have been reported. What is New: • The presence of clowns in the waiting room and in the ED during medical evaluation and painful procedures helps to reduce children's anxiety.

Quality of maternal and neonatal care in Albania, Turkmenistan and Kazakhstan: a systematic, standard-based, participatory assessment. - Tamburlini, Giorgio; Siupsinskas, Gelmius; Bacci, Alberta (PLoS One, 2011)
BACKGROUND: Progress in maternal and neonatal mortality has been slow in many countries despite increasing access to institutional births, suggesting deficiencies in the quality of care. We carried out a systematic assessment of the quality of maternal and newborn care in three CEE/CIS countries, using an innovative approach to identify priority issues and promote action. METHODS: A standard-based tool, covering over 400 items grouped in 13 main areas ranging from support services to case management, was used to assess a sample of ten maternity hospitals in Albania, Kazakhstan and Turkmenistan. Sources of information were visit to services, medical records, observation of cases, and interviews with staff and mothers. A score (range 0 to 3) was attributed to each item and area of care. The assessment was carried out by a multidisciplinary team of international and national professionals. Local managers and staff provided the necessary information and were involved in discussing the findings and the priority actions. RESULTS: Quality of care was found to be substandard in all 13 areas. The lowest scores (between one and two) were obtained by: management of normal labour, delivery, obstetric complications and sick babies; infection prevention; use of guidelines and audits; monitoring and follow-up. Neonatal care as a whole scored better than obstetric care. Interviewed mothers identified lack of information, insufficient support during labour and lack of companionship as main issues. Actions to improve quality of care were identified at facility as well as at central level and framed according to main health system functions. CONCLUSIONS: Quality of care is a key issue to improve maternal and neonatal outcomes, particularly in countries such as CEE/CIS where access to institutional births is nearly universal. Approaches that involve health professionals and managers in comprehensive, action-oriented assessments of quality of care are promising and should be further supported.
Keywords: Albania; Child Health Services; Female; Humans; Infant, Newborn; Kazakhstan; Maternal Health Services; Pregnancy; Quality of Health Care; Turkmenistan

Quantification of heteroplasmic mitochondrial DNA mutations for DNA samples in the low picogram range by nested real-time ARMS-qPCR. - Biffi, Stefania; Bortot, Barbara; Carrozzi, Marco; Severini, Giovanni Maria (Diagn Mol Pathol, 2011)
In many mitochondrial diseases, different clinical manifestations are related to tissue-specific distribution of mutated mitochondrial DNA (mtDNA). In this study, we describe an assay for the determination of mutated mtDNA copy number in small clinical samples, using standard polymerase chain reaction (PCR) followed by SYBR Green real-time allelic-specific PCR [amplification refractory mutation system-quantitative PCR (ARMS-qPCR)]. To assess the degree of heteroplasmy in a patient harboring 2 cosegregating mtDNA mutations (4415A>G and 9922A>C) starting from picogram amounts of DNA, we first amplified the mutated target sequence by standard PCR, and then analyzed it by real-time ARMS-qPCR. To validate this method, we analyzed by real-time ARMS-qPCR the PCR amplification products derived from different mixtures containing known proportions of mutant and wild-type cloned mtDNA fragments. The correlation coefficient of 0.994 between expected and observed values for the percentage of mutant A4415G confirms that the relative proportion of mutated and wild-type mtDNA was maintained after the first PCR amplification. This method allows the precise quantification of heteroplasmic mutations in DNA samples extracted from hairs, urine, small stomach biopsies, and, more importantly, single-muscle fiber, with a limit of detection close to 0.5%. This nested real-time ARMS-PCR represents a rapid, efficient, and less expensive method for the detection and quantification of heteroplasmic mutant mtDNA, even in very small clinical samples.
Keywords: Child; DNA, Mitochondrial; Humans; Mitochondrial Diseases; Mutation; Polymerase Chain Reaction; Sensitivity and Specificity